2002
DOI: 10.1034/j.1600-0633.2002.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Prey size selection in piscivorous pikeperch (Stizostedion lucioperca) includes active prey choice

Abstract: – Knowledge of the mechanisms behind prey selection in piscivorous fish is important for our understanding of the dynamics of freshwater systems. Prey selection can involve active predator choice or be a passive process. We experimentally studied size‐selectivity in pikeperch, feeding on roach and rudd. When given a choice of different prey sizes, pikeperch selected small prey. Passive selection mechanisms (encounter rate, capture success and satiation) could not fully explain the pattern of diet choice. Inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 55 publications
3
77
1
4
Order By: Relevance
“…3 está diretamente relacionado ao sucesso no forrageamento, pois a resposta de fuga da presa é altamente correlacionada com o tamanho do corpo, que conforme aumenta, melhora a performance de natação. A seleção de uma presa pelo tamanho específico, provavelmente seja mais importante que a seleção pelo tipo de presa (Tonn et al 1992, Juanes et al 2002, uma vez que em ambientes aquáticos, o tamanho é um dos principais determinantes da taxa de encontro ou sucesso de captura (Turesson et al 2002). Assim, a teoria de forrageamento ótimo prediz que o predador consome presas que tenham maior valor energético e que possam maximizar o seu fitness (Gerking 1994).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…3 está diretamente relacionado ao sucesso no forrageamento, pois a resposta de fuga da presa é altamente correlacionada com o tamanho do corpo, que conforme aumenta, melhora a performance de natação. A seleção de uma presa pelo tamanho específico, provavelmente seja mais importante que a seleção pelo tipo de presa (Tonn et al 1992, Juanes et al 2002, uma vez que em ambientes aquáticos, o tamanho é um dos principais determinantes da taxa de encontro ou sucesso de captura (Turesson et al 2002). Assim, a teoria de forrageamento ótimo prediz que o predador consome presas que tenham maior valor energético e que possam maximizar o seu fitness (Gerking 1994).…”
Section: Discussionunclassified
“…De acordo com Turesson et al (2002), a predação seletiva é uma característica comum entre a maioria dos predadores e tem sido alvo de muitos estudos. Um dos principais fatores que interferem na escolha do alimento pelos peixes é a sua disponibilidade no ambiente, sendo que para as espécies piscívoras, que perseguem suas presas em movimento, a coincidência de eco-áreas, o tipo de comportamento, a atividade e o tamanho das presas, tornam-se, também, fatores muito importantes (Popova, 1978).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…It is believed that this is determined by the lower risk of failure to catch them. Those who are larger swim vigorously and cause real danger of kleptoparasitism (Nilsson and Bronmark, 1999;2000;Tuersson et al, 2006). The opposite conclusion is reached by Hubenova et al (2013), who found that pike prefers to feed on larger specimens.…”
Section: Introductionmentioning
confidence: 92%
“…Predation may affect prey populations both directly and indirectly. The direct effects of predation can include the death and/or injury of the prey (Wootton, 1990), the reduction of prey abundance or changes in the prey size-frequency distribution (Turesson et al, 2002). Behavioural alterations in a prey species under predation risk can be an indirect effect of predation.…”
Section: Introductionmentioning
confidence: 99%